Molecular characterization of Cryptosporidium in wild rodents from the Inner Mongolian Autonomous Region and Liaoning Province, China: assessing host specificity and the potential for zoonotic transmission - Liu, Li; Xu, Qunfang; Jiang, Aiying; Zeng, Fansheng; Zhao, Wei; Tan, Feng (Frontiers in Veterinary Science, 2024)
Wild rodents are key hosts for Cryptosporidium transmission, yet there is a dearth of information regarding their infection status in the Inner Mongolian Autonomous Region and Liaoning Province of China.Therefore, the present study was conducted to determine the prevalence and genetic characteristics of Cryptosporidium among wild rodents residing in these two provinces. A total of 486 rodents were captured, and fresh feces were collected from each rodent's intestine for DNA extraction. Species identification of rodents was performed through PCR amplification of the vertebrate cytochrome b (cytb) gene. To detect the presence of Cryptosporidium in all fecal samples, PCR analysis and sequencing of the partial small subunit of the ribosomal RNA (rRNA) gene were performed. Four species of rodents were identified: Rattus norvegicus, Mus musculus, Apodemus agrarius, and Cricetulus barabensis. Positive results for Cryptosporidium were obtained for 9.2% (18/195), 6.6% (7/106), 5.6% (5/89), and 6.3% (6/96) of these rodents, respectively, with an average infection rate of 7.4% ( 36/486). The identification revealed the presence of five Cryptosporidium species, C. ubiquitum (n = 8), C. occultus (n = 5), C. muris (n = 2), C. viatorum (n = 1), and C. ratti (n = 1), along with two Cryptosporidium genotypes: Rat genotype III (n = 10) and Rat genotype IV (n = 9). Based on the molecular evidence presented, the wild rodents investigated were concurrently infected with zoonotic (C. muris, C. occultus, C. ubiquitum and C. viatorum) as well as rodent-adapted (C. ratti and Rat genotype III and IV) species/genotypes, actively participating in the transmission of cryptosporidiosis.